INVESTIGATION OF PHYSICAL AND MECHANICAL PROPERTIES OF FRICTION STIR WELDING ON ALUMINUM 6092/SIC/25P/T6 WELDED PLATES - PATTHI, UMAR (2013)
Friction Stir Welding (FSW) is a relatively new welding technique and itsphysics is still not widely known. Compared to fusion welding, this technique reduces problem associated with metal re-solidification as the technique involves no melting stages suitable for joining high strength aerospace material such as aluminum metal matrix composite (AMMC). Initially FSW had been developed and successfully applied for welding softer material such as aluminum alloy. Scarce research had been conducted on FSW of AMMC where the material have a higherstiffness, strength and wear resistance compared to monolithic aluminum alloy. Research of FSW on aluminum 6092 series reinforce with 25% discontinuous SiC particles volume with T6 ageing (aluminum 6092/SiC25P/T6) has not been reported.